Tattooed on My Soul : Texas Veterans Remember World War II - Holland, Michelle, 1982-; Myers, Lois E., 1946-; Sloan, Stephen M. (Book collections on Project MUSE., 2015)
"For more than forty years the Oral History Institute at Baylor University has dutifully gathered the flesh-and-blood memories of the World War II generation in the state of Texas to ensure that the personal experiences of those pivotal years would be preserved--for them, for their families, and for future generations. Tattooed on My Soul brings together seventeen of the most compelling narratives from Baylor's extensive collection of more than five thousand interviews"--ECIP Data View summary.